Electronic version of the information module of medical record in surgical pathology - M. G. Daryina; K. N. Movchan; B. S. Artyushin; R. B. Iskhakov; Ju. S. Svetlichnaya; E. R. Tsoy; K. I. Rusakevich; Yu. N. Savushkin; R M. Gedgafov (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2019)
Introduction. The need for software for targeted epidemiological monitoring of patients with high risk of infection in surgical procedures is obvious at present.The objective of the study was the scientific substantiation of the content of the epidemiological module of the electronic medical records of patients with surgical diseases.Material and methods. Retrospective analysis of data on infectious complications in the area of surgical intervention in patients of 42 hospitals of St. Petersburg over the past 10 years.Results. The incidence rate of surgical sites infections in hospitals of St. Petersburg for many years did not exceed 0.3 per 100 operations, due to the lack of reliable monitoring data of observations of postoperative infectious complications in the city institutions. We defined the list of parameters to be recorded in the electronic medical record during surgical treatment of pathology for the organization of systematic monitoring of the course of pathophysiological changes in the area of operation, taking into account the overall clinical assessment of the quality of medical care.Conclusion. The use of the epidemiological module in the electronic medical record would allow timely and purposefully to carry out preventive measures on creating conditions for the uncomplicated course of the postoperative period in patients who underwent surgery in the hospital.